2016
DOI: 10.1002/ange.201601091
|View full text |Cite
|
Sign up to set email alerts
|

Zielgerichtete kovalente Inhibitoren für das Wirkstoffdesign

Abstract: Abweichend vom üblichen Arzneimittelwirkmechanismus einer reversiblen, nichtkovalenten Wechselwirkung eines Liganden mit seinem biologischen Zielmolekül wird ein zielgerichteter kovalenter Inhibitor (TCI) so entwickelt, dass nach einer anfänglichen reversiblen Assoziation eine kovalente Bindung zwischen einem Elektrophil auf dem Liganden und einem nucleophilen Zentrum auf dem Protein geknüpft wird. Obwohl diese Methode einige potenzielle Vorteile bietet (hohe Wirksamkeit, verlängerte Wirkung), haben Bedenken w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…The main pathological hallmarks of PD are the loss of dopaminergic neurons and the presence of eosinophilic inclusions, called Lewy bodies (LB), in the substantia nigra parsc ompacta of the midbrain. In recent years, there has been ar esurgence of interest in covalent inhibitors, [11] and the 2-cyanoacrylamide group can [a] Dr. In recent years, many researchers have reported that GSK-3b is implicated in microglial-mediated inflammation.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The main pathological hallmarks of PD are the loss of dopaminergic neurons and the presence of eosinophilic inclusions, called Lewy bodies (LB), in the substantia nigra parsc ompacta of the midbrain. In recent years, there has been ar esurgence of interest in covalent inhibitors, [11] and the 2-cyanoacrylamide group can [a] Dr. In recent years, many researchers have reported that GSK-3b is implicated in microglial-mediated inflammation.…”
mentioning
confidence: 99%
“…In recent years, many researchers have reported that GSK-3b is implicated in microglial-mediated inflammation. In recent years, there has been ar esurgence of interest in covalent inhibitors, [11] and the 2-cyanoacrylamide group can [a] Dr. [3] Furthermore, GSK-3b and CK-1d are responsible for the phosphorylation of proteins that are abundant in the LB, including tau, a-synuclein, and parkin.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found, that under certain conditions, the properties of covalent drugs could prove beneficial when compared with their noncovalent equivalents. 8 For instance, due to the longlasting effects of a covalent drug, it is able to inhibit the same biological target at a lower concentration than a noncovalent drug. 9,10 An example of this covalent reaction (Michael addition) between a ligand, subject of this study, and its protein target is shown in Figure 1.…”
mentioning
confidence: 99%